Makna Teologis-Tekstual Tujuh Perkataan Yesus di Kayu Salib dan Implikasinya Terhadap Spiritualitas Pelayanan Kristiani - Marthen Mau; Henni Somantik (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
The statements of Jesus on the cross represent a deeply theological aspect that must continue to be studied, understood, and applied in today’s Christian ministry. Christian ministry must not ignore the meaning of Jesus’ holy suffering as an expression of His sacrifice to redeem sinful humanity. Unfortunately, there are still some who question the authenticity of this suffering, even believing that the one who was crucified was not Jesus, but one of His disciples or another person. This perspective stands in opposition to the core teachings of the Christian faith.This study aims to narrate the peak quality of Jesus’ holy suffering through His seven last sayings on the cross. The research uses a qualitative method with a library research approach and grammatical analysis of biblical texts. Data were collected from theological literature and analyzed in light of biblical implications concerning the idea of Jesus’ suffering.The findings show that each statement of Jesus on the cross holds profound theological meaning and reflects God’s eternal plan for the redemption of human sin. A grammatical analysis of these texts strengthens the understanding that Jesus’ suffering is not only a historical event but also bears a deep spiritual significance essential for human salvation. Therefore, the teaching of Jesus’ words on the cross must become an integral part of church ministry today to strengthen the faith of believers in the truth of the Gospel.